Application of Information and Communication Technologies in School Religion Teaching in the Light of the Latest Catechetical Documents - Bielinowicz, Adam Przemysław (Studia Warmińskie, 2021)
The technological revolution that has taken place in recent decades affects virtually all areas of life, has also crossed the doors of schools. Contemporary teachers, including catechists, are usually IT competent people who successfully use digital tools in their work. This situation should be reflected in the most recent catechetical documents containing the fundamental principles and guidelines that shape the teaching of religion. This paper presents the results of the analysis of three documents: Directory on Catechesis, Fundamentals of Catechesis of the Catholic Church in Poland, and Curriculum for the Roman Catholic Religion in Kindergartens and Schools. The author also proposes some solutions for catechetical service in relation to the user of information and communication technologies in school teaching of religion.